Hubungan Pola Asuh Orang Tua dengan Status Gizi pada Remaja di SMAN 9 Depok - Nourmayansa Vidya Anggraini; Diah Tika Anggraeni; Mareta Dea Rosaline; Rahmatika Syifa Nabila (Universitas Malahayati Lampung, 2025)
ABSTRACT Adolescents are very vulnerable to various nutritional problems because in this phase growth and development occur very quickly and tend to require relatively large amounts of nutritional intake. Based on the results of a preliminary study of 35 adolescents, 4 students with poor nutritional status, 4 students with undernutrition, 19 students with normal nutritional status, 2 students with overnutrition, and 6 students with obese nutritional status were found. This study aims to determine the relationship between parenting patterns and adolescent nutritional status at SMAN 9 Depok. The method used is this non-experimental quantitative research with a descriptive correlational design and using a cross sectional study approach. The sample used amounted to 246 samples obtained through the Stratified Random Sampling technique. Data were obtained by measuring height and weight and filling out a structured questionnaire. The results of the analysis with the gamma correlation test showed that there was a relationship between parenting patterns and nutritional status in adolescents with a p-value: 0.001 with a contribution value of 16.7%. Mass media plays an important role in adolescent nutritional behavior. Parents should monitor the use of mass media by teenagers so that positive things are taken by teenagers in their use. Keywords: Nutrition, Mass Media, Obesity, Youth ABSTRAK Remaja sangat rentan terhadap berbagai masalah gizi karena pada fase ini pertumbuhan dan perkembangan terjadi sangat cepat dan cenderung memerlukan asupan nutrisi dalam jumlah yang relatif besar. Berdasarkan hasil studi pendahuluan kepada 35 remaja didapatkan 4 siswa dengan status gizi buruk, 4 siswa dengan status gizi kurang, 19 siswa dengan status gizi normal, 2 siswa dengan status gizi lebih, dan 6 siswa dengan status gizi obesitas. Penelitian ini bertujuan untuk mengetahui hubungan antara pola asuh orang tua dengan status gizi remaja di SMAN 9 Depok. Metode yang digunakan yaitu penelitian kuantitatif non eksperimental ini dengan desain deskriptif korelasional serta menggunakan pendekatan study cross sectional. Sampel yang digunakan berjumlah 246 sampel yang didapatkan melalui teknik Stratified Random Sampling. Data didapatkan dengan melakukan pengukuran tinggi dan berat badan serta pengisian kuesioner terstruktur. Hasil analisis dengan uji korelasi gamma menunjukkan bahwa terdapat hubungan antara pola asuh orang tua dengan status gizi pada remaja dengan nilai p- value : 0.001 dengan nilai kontribusi sebesar 16.7%. Diharapkan para orang tua dapat meningkatkan pengetahuan mereka tentang pola asuh ideal. Kata Kunci: Gizi, Media Massa, Obesitas, Remaja